Calculation of Optimum Insulation Thickness and Energy Savings for Different Climatic Regions of Turkey - Akpınar, Ebru Kavak; Demir, İbrahim Halil (Fırat University, 2018)
In this study, the optimum insulation thickness, energy savings and payback periods were calculated based on life-cycle cost analysis for the cities of Balıkesir, Kayseri, Malatya, Mersin, Muğla, Şanlıurfa and Trabzon. These cities were selected from Turkey’s four climate zones. The calculations were carried out for coal as energy source, expanded polystyrene (EPS) and extruded polystyrene (XPS) as insulation materials on two types of walls: (1) sandwich and (2) externally insulated. Results indicated that insulation thicknesses varied between 0.002–0.049 m, with the amount of life-cycle energy saving as 0.629–21.047 $/m2 and a payback period of 0.3–6.5 years depending on the type of fuel, insulation material and wall-type. In this study, the optimum insulation thickness, energy savings and payback periods were calculated based on life-cycle cost analysis for the cities of Balıkesir, Kayseri, Malatya, Mersin, Muğla, Şanlıurfa and Trabzon. These cities were selected from Turkey’s four climate zones. The calculations were carried out for coal as energy source, expanded polystyrene (EPS) and extruded polystyrene (XPS) as insulation materials on two types of walls: (1) sandwich and (2) externally insulated. Results indicated that insulation thicknesses varied between 0.002–0.049 m, with the amount of  life-cycle energy saving as 0.629–21.047 $/m2 and a payback period of 0.3–6.5 years depending on the type of fuel, insulation material and wall-type.